S21.3 Authentic and successful community engagement for STI/HIV prevention, screening and treatment in rural and urban settings. (14th July 2019) - Rhodes, Scott
Abstract : Sexually transmitted infections (STIs) and HIV remain critical public health challenges in the United States. There is a clear need for innovative approaches that identify, prioritize, and address underlying 'upstream' social determinants of health while developing and harnessing community assets to improve STI and HIV prevention, screening, and treatment. Community engagement has emerged as an approach to improve public health outcomes, including reduced STIs and HIV. However, community engagement is difficult, and this presentation provides guidance on the characteristics and strategies of authentic and successful community engagement designed to promote STI and HIV prevention, screening, and treatment in both rural and urban settings. Members of our community partnerships used mixed-methods to identify characteristics of successful community engagement and associated strategies across more than 30 STI and HIV initiatives across the United States. We abstracted data from existing project documentation including proposal documents, project-specific logic models, team and partnership meeting notes, and other materials. Partnership members examined these documents and used an iterative approach with review, discussion, and re-review. A component of our analysis was to identify characteristics and strategies that crossed initiatives, had potential to be generalizable, and could guide future STI and HIV initiatives. Some of the characteristics and strategies that were identified included, staff/team knowledge and unflagging commitment to community engagement; understanding of and commitment to social justice; structural flexibility; strong and charismatic institutional leadership; participation of partners representing diverse multiple sectors; recognizing, acknowledging, and reducing power differentials; shared decision making; embracing and working through conflict; identifying and leveraging talent, strengths, and resources; and using a stepwise approach to build a shared history. Often and incorrectly conflated with advisory boards, qualitative methods, and behavioral and social sciences more broadly, community engagement requires careful forethought, the use of inclusive processes that bring together diverse constituencies, and shared resources and power. Disclosure: No significant relationships.